2012
DOI: 10.1159/000258197
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106b and MiR-15b Modulate Apoptosis and Angiogenesis in Myocardial Infarction

Abstract: Background: MicroRNAs (miRNAs) are identified as crucial gene regulators in response to myocardial infarction (MI). However, the overall relationships between miRNAs and the gene targets which contribute to the cellular phenotypes in MI are not fully elucidated. To make a better understanding towards functional roles of miRNAs in MI, useful information was mined through bioinformatic techniques. Method: MI-related miRNAs were retrieved from publications, and PicTar, TargetScanS, and miRanda programs were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 54 publications
4
55
0
Order By: Relevance
“…MiR-15b has been associated with apoptosis and angiogenesis in myocardial infarction. 42 MiR-27b has been identified as a proangiogenic miRNA, 43 regulating angiogenesis through the angiogenic inhibitor semaphorin 6A. 44 MiR-126 is known to regulate angiogenic signaling and vascular integrity, 45 and miR-16 has been found to play a role in angiogenesis by reducing the proliferation, migration, and angiogenic capacity of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-15b has been associated with apoptosis and angiogenesis in myocardial infarction. 42 MiR-27b has been identified as a proangiogenic miRNA, 43 regulating angiogenesis through the angiogenic inhibitor semaphorin 6A. 44 MiR-126 is known to regulate angiogenic signaling and vascular integrity, 45 and miR-16 has been found to play a role in angiogenesis by reducing the proliferation, migration, and angiogenic capacity of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other than our previously described candidates, miR-100 7 and miR-214, 10 other already well characterized modulators of blood vessel growth are among the top upregulated and downregulated genes, such as miR-106b, 8 miR-21, 9 miR-378, 21 miR-29c, 22 miR30e, 23 and miR-98 24 , whereby the last 4 named miRNAs are mainly known to modulate tumor angiogenesis. The validity of our screening approach is supported by the fact that Greco et al 25 also identified miR-29c as a downregulated miRNA in a similar setting.…”
Section: Discussionmentioning
confidence: 72%
“…Our hierarchical list of top regulated miRNAs (Tables 1 and 2) included previously described miRNA modulators of neovascularization, such as miRNA-100, 7 miRNA-106b, 8 miRNA-21, 9 and miRNA-214. 10 In addition, our experiment revealed a strong downregulation of miR-155, for which the role in adaptive blood vessel growth was so far unknown.…”
Section: Mirna Expression Profiling Reveals Mir-155 Downregulation Dumentioning
confidence: 99%
“…By highlighting miRNA-gene networks, overall relationships between miRNAs and gene targets were discovered, particularly in apoptosis and angiogenesis. Experimental data identified miR-106b as an anti-apoptotic modulator through inhibition of p21 expression and miR-15b as an anti-angiogenic miRNA with the possible targets vascular endothelial growth factor and Ang2 (angiopoietin 2) [30] . All miRNAs with suggested role in angiogenesis in MI are summarized in Figure 2.…”
Section: Mirna In Myocardial Infarctionmentioning
confidence: 99%